IMMUNOLOGICAL AND ENVIRONMENTAL DETERMINANTS OF ADENOID VEGETATIONS AND TONSILLAR HYPERTROPHY IN CHILDREN - Abdusamatova Iroda Ilkhamovna; Pardayev Chori Ikhtiyor ugli; Ismoilov Dilmurod Gulom ugli; Ismoilov Dilmurod Gulom ugli; Hamroyeva Zarina Muhiddin qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Adenoid vegetations and tonsillar hypertrophy are among the most common pediatric ENT conditions, significantly affecting respiratory function, immunity, and quality of life. According to international data, approximately 25–45% of children experience clinically significant adenoid hypertrophy, often associated with recurrent infections and allergic conditions. This study aims to evaluate immunological and environmental determinants contributing to adenotonsillar enlargement and dysfunction. A total of 130 children (100 patients and 30 controls) were examined using clinical, laboratory, and instrumental methods. The findings indicate that immune imbalance, allergen exposure, and recurrent infections are key contributors to disease development. The study emphasizes the importance of комплекс preventive strategies and early intervention.